Respuesta :

Solve for x over the real numbers:
4 x^4 + 31 x^3 - 4 x^2 - 89 x + 22 = 0

The left hand side factors into a product with three terms:
(x + 2) (4 x - 1) (x^2 + 6 x - 11) = 0

Split into three equations:
x + 2 = 0 or 4 x - 1 = 0 or x^2 + 6 x - 11 = 0

Subtract 2 from both sides:
x = -2 or 4 x - 1 = 0 or x^2 + 6 x - 11 = 0

Add 1 to both sides:
x = -2 or 4 x = 1 or x^2 + 6 x - 11 = 0

Divide both sides by 4:
x = -2 or x = 1/4 or x^2 + 6 x - 11 = 0

Add 11 to both sides:
x = -2 or x = 1/4 or x^2 + 6 x = 11

Add 9 to both sides:
x = -2 or x = 1/4 or x^2 + 6 x + 9 = 20

Write the left hand side as a square:
x = -2 or x = 1/4 or (x + 3)^2 = 20

Take the square root of both sides:
x = -2 or x = 1/4 or x + 3 = 2 sqrt(5) or x + 3 = -2 sqrt(5)

Subtract 3 from both sides:
x = -2 or x = 1/4 or x = 2 sqrt(5) - 3 or x + 3 = -2 sqrt(5)

Subtract 3 from both sides:
Answer:  x = -2 or x = 1/4 or x = 2 sqrt(5) - 3 or x = -3 - 2 sqrt(5)

The real roots of a function are the rational and the irrational roots of the function

The real roots are: [tex]\mathbf{x = -2}[/tex], [tex]\mathbf{x = \frac 14}[/tex], [tex]\mathbf{x = -3 - 2\sqrt{5}}[/tex] and [tex]\mathbf{x = -3 + 2\sqrt{5}}[/tex]

The equation is given as:

[tex]\mathbf{ 4x^4+31x^3-4x^2-89x+22=0}[/tex]

Factorize

[tex]\mathbf{(x + 2) (4 x - 1) (x^2 + 6 x - 11) = 0}[/tex]

Split

[tex]\mathbf{x + 2 = 0\ or\ 4 x - 1 = 0 \ or\ x^2 + 6 x - 11 = 0}[/tex]

Solve for x

[tex]\mathbf{x = -2\ or\ x = \frac 14 \ or\ x^2 + 6 x - 11 = 0}[/tex]

Solve

[tex]\mathbf{x^2 + 6 x - 11 = 0}[/tex] using the following quadratic formula:

[tex]\mathbf{x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}}[/tex]

So, we have:

[tex]\mathbf{x = \frac{-6 \pm \sqrt{6^2 - 4 \times 1 \times -11}}{2 \times 1}}[/tex]

[tex]\mathbf{x = \frac{-6 \pm \sqrt{80}}{2}}[/tex]

[tex]\mathbf{x = \frac{-6 \pm 4\sqrt{5}}{2}}[/tex]

[tex]\mathbf{x = -3 \pm 2\sqrt{5}}[/tex]

Hence, the real roots are:

[tex]\mathbf{x = -2}[/tex], [tex]\mathbf{x = \frac 14}[/tex], [tex]\mathbf{x = -3 - 2\sqrt{5}}[/tex] and [tex]\mathbf{x = -3 + 2\sqrt{5}}[/tex]

Read more about real roots at:

https://brainly.com/question/21664715